2004
DOI: 10.1021/ie034294j
|View full text |Cite
|
Sign up to set email alerts
|

Product and Process Development via Sequential Pseudo-Uniform Design

Abstract: The application of the uniform design (UD) method to nonlinear multivariate calibration by an artificial neural network (ANN) can be used to build a model for an unknown process efficiently because it allows many levels for each factor. If the cost of each experiment is high, low partitioned levels are usually proposed first to carry out the experiments. However, if a reliable ANN model cannot be obtained from the designed experiments, the sequential pseudo-uniform design (SPUD) method developed here can be em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Their UD results in simulated and real fluorescence systems were satisfactory. Chang and Lin developed the sequential pseudo‐UD method to locate additional experiments in the experimental region. Their simulation results demonstrated that the product and process development based on the proposed method only required a reasonable number of experiments.…”
Section: Applications Of Uniform Designmentioning
confidence: 99%
“…Their UD results in simulated and real fluorescence systems were satisfactory. Chang and Lin developed the sequential pseudo‐UD method to locate additional experiments in the experimental region. Their simulation results demonstrated that the product and process development based on the proposed method only required a reasonable number of experiments.…”
Section: Applications Of Uniform Designmentioning
confidence: 99%
“…To determine the possible optima of an unknown process, an experimental design scheme that uses UD, SPUD, artificial neural networks (ANN), and random search was proposed in our previous studies. , The main objective of the proposed experimental design scheme is to build a reliable model and locate the optima of an unknown process simultaneously using only a reasonable number of experiments. Presently, the most commonly used ANN type is a multilayer artificial feed-forward neural network (FNN), which is trained by the back-propagation (BP) algorithm.…”
Section: Construction Of Data-driven Model For Process Optimizationmentioning
confidence: 99%
“…For an unknown complex process, one usually uses the experimental design to arrange effective experiments to obtain process information from a small-scale system. When the amount of experimental information is enough to construct a reliable model, the optimal recipe and operating conditions of the small-scale system could be obtained effectively on the basis of the constructed data-driven model. ,, Similarly, if the data-driven model is built from the experimental data eventually taken from a scale-up system, the optimal recipe and operating conditions could be determined accordingly if the cost of the experimental resources is not an important issue. In general, the optimal recipe and operating conditions for a small-scale system may not be necessarily the same as those for the scale-up system.…”
Section: Introductionmentioning
confidence: 99%
“…To provide an identified HNNRF model with rich information, the developed sequential pseudo-uniform design (SPUD) method [20] will be applied to locate limited but sufficient experiments for gathering the experimental data. The developed SPUD method is an extended version of the uniform design (UD) method [21].…”
Section: Neural Network Trainingmentioning
confidence: 99%
“…The developed SPUD method is an extended version of the uniform design (UD) method [21]. With respect to the detail of the SPUD method, one could make reference to our previous work [20]. In this work, the experiments for gathering the training data based on the UD method will be performed at first.…”
Section: Neural Network Trainingmentioning
confidence: 99%